Distribution of Risks for Major Osteoporotic Fracture Based on Fracture Risk Assessment Tool in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Nik Fatin Farhana Binti Mohd Rahhim; Bambang Tiksnadi; Eppy Buchori (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Osteoporosis has become a growing public health problem in Indonesia. A definite estimation of osteoporosis prevalence in Indonesia is not available due to the limited access of dual energy X ray absorptiometry (DXA) facilities. In 2008, the World Health Organization has developed a tool called Fracture Risk Assessment Tool to identify fracture risk based on the clinical risk factors. The study aimed to identify the risk factors of osteoporotic fracture using Fracture Risk Assessment Tool in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.Methods: This descriptive study was conducted from June–December 2013 in Orthopedic & Traumatology, Internal Medicine, Geriatric and Surgery polyclinics Dr. Hasan Sadikin General Hospital, Bandung to 77 respondents, aged 40–90 years, using the random sampling method. Fracture risks were calculated online, and the data obtained were analyzed and presented using frequency distribution in tables.Results: Most of the respondents had low risk for osteoporotic fracture, and only 5.19% of them had moderate risk. The main risk factors were rheumatoid arthritis (57.14%), followed by current smoking (27.27%) and prolonged glucocorticoids consumption (25.98%). The moderate risk group was females, above 60 years old and with normal BMI or underweight with risks of previous fracture, parent’s previous hip fracture, rheumatoid arthritis and prolonged glucocorticoids exposure.Conclusions: Majority of the respondents have low risk for osteoporotic fracture. It must be taken into consideration that increasing age, rheumatoid arthritis, current smoking, prolonged glucocorticoids consumption, previous fracture and parent’s previous hip fracture can cause increased risk. DOI: 10.15850/amj.v2n3.514